From perfluoroalkyl aryl sulfoxides to ortho thioethers - Li, Yang; Dagousset, Guillaume; Magnier, Emmanuel; Pégot, Bruce (Beilstein Journal of Organic Chemistry, 2024)
Access to original ortho thioether derivatives was achieved through a [3,3]-rearrangement in a one-pot two-step protocol. Several aryl-SCF3 compounds are reported by variation of the nitrile or of the trifluoroalkyl sulfoxide starting material. The variation of the perfluoroalkyl chain was also possible.
Keywords: ortho functionalization; rearrangement; sulfoxide